2005
DOI: 10.1115/1.2165691
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Local Blood Flow in the Carotid and Cerebral Arteries Under Altered Gravity

Abstract: A computational fluid dynamics (CFD) approach was presented to model the blood flows in the carotid bifurcation and the brain arteries under altered gravity. Physical models required for CFD simulation were introduced including a model for arterial wall motion due to fluid-wall interactions, a shear thinning fluid model of blood, a vascular bed model for outflow boundary conditions, and a model for autoregulation mechanism. The three-dimensional unsteady incompressible Navier-Stokes equations coupled with thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 20 publications
1
41
1
Order By: Relevance
“…The peak systolic WSR values measured in vivo with the proposed method are higher than those typically reported in the literature for the common carotid arteries (11,(13)(14)(15)(16)20,22) but within the range of normal values in healthy individuals (1,3,21,(28)(29)(30)(31). Reported ranges of carotid WSR and WSS values in healthy volunteers vary significantly across the literature, in particular when comparing different techniques (11).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The peak systolic WSR values measured in vivo with the proposed method are higher than those typically reported in the literature for the common carotid arteries (11,(13)(14)(15)(16)20,22) but within the range of normal values in healthy individuals (1,3,21,(28)(29)(30)(31). Reported ranges of carotid WSR and WSS values in healthy volunteers vary significantly across the literature, in particular when comparing different techniques (11).…”
Section: Discussionmentioning
confidence: 80%
“…PC is not currently capable of providing accurate absolute measurements of WSS (18) and has been shown to underestimate blood flow velocities in the carotid bifurcation by 31-39% (19). An alternative approach for estimating WSS is to reconstruct a complex flow field via computational fluid dynamics (CFD) simulation, using vascular geometries and input/output functions derived from noninvasive imaging data (20)(21)(22). This approach is computationally intense and may be sensitive to many assumptions and simplifications that are frequently made about the properties of blood and endothelium.…”
mentioning
confidence: 99%
“…Moreover, the devices resolution is not compatible with the precision required to discriminate the spatial parabolic blood flow profile (see Fig 1) the robot faces depending on its position in the vessel. Another solution relies on a priori knowledge of the blood velocity, either using computational solutions of the Navier Stokes equation [14], or analytical expressions of the blood velocity profiles [10]. However, the former is not well suited for real-time purposes, whilst the latter requires a precise a priori knowledge of the vessel geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Moore et al [17,18] modelled three anatomical variations and showed the flow redistribution with these anatomical variations. Kim et al [19,20] modelled three patient-specific geometries and found communicating arteries play an important role in the cerebral autoregulation mechanism. Alnaes et al [21] modelled three geometric variants of the posterior part of the CoW and showed that differences in vessel radii and bifurcation angle influence the wall shear stress.…”
mentioning
confidence: 99%